Influence of Influencer Marketing and Event Marketing in Order to Build Tokopedia Brand Loyalty - Didi Tarmidi; Lulu Jane Rimba (Institute of Computer Science (IOCS), 2022)
Maintaining consumer loyalty to the brand is the main important task that must be in the marketing strategy to maintain the company's sales and revenue especially if the company is e-commerce in Indonesia such as Tokopedia. This study will reveal how the influence of variable influencer marketing and Tokopedia marketing events in building consumer brand loyalty. This research method uses a quantitative approach with survey instruments then described in descriptive analysis. At the end of the study, it was shown that the results of both variable influencer marketing and event marketing had a significant impact on the loyalty of 46.3%. Further reviewed influencer marketing, influencer marketing encourages consumers to routinely review marketing events on the Tokopedia application and then marketing events also help consumers visit longer with offers at a limited time in certain product categories – certain products encourage consumers to keep using Tokopedia as an option in shopping.